Modernization of public administration in Eastern Europe in the context of implementation of digitalization - Shashyna, Maryna; Gudz, Petro; Pankova, Alla; Benchak, Olesia; Nemyrovska, Oksana (Eastern-European Journal of Enterprise Technologies, 2023)
The European Union is taking significant steps and supporting the efforts of member countries to improve the quality of public services. The requirements for the digitization of the latter, to improve communication links, highlight the relevance of the research topic by shifting the emphasis to the indirect assessment of the impact of technology transfer in the field of public administration on citizens’ satisfaction with public services. The object of research in this work is the public administration models of the selected countries. The research hypothesis assumes that membership in the EU has a significant impact on the efficiency of public services. Given this, there is an opportunity to transfer technologies, namely technologies of state management. The countries of Eastern Europe were selected for the study. The work is based on the limitations inherent in the EU accession process. For evaluation, three regression models were proposed for use in practice. These are a baseline model, a fixed-effects model to account for unobserved differences between countries, and a model with additional factors. The specified models were estimated using the least-square method (LSM). Based on the calculations of the first model, it was determined that the coefficient is statistically significant at the level of 1 %, which explains 12.6 % of the variation in the Index of Public Services (IPS). The results of the estimation of the second model make it possible to estimate IPS more accurately by 0.68. Based on the results of the calculation of the third model, the features of the influence of GDP and IPS were determined. The results prove that the accession of Eastern European countries to the EU has a significant impact on the efficiency of public services. In this case, the possibility of technology transfer appears. Digitization of public administration is an innovative technology that allows bringing the citizen and the state closer together as efficiently as possible